The Possible Potentials of Astrotourism in Caucasus - Mohammad Javad Torabi
Astrotourism is not a new topic, but it is certainly a title that has been in the forefront of tourism and astronomy for less than two decades. For nearly half a century, observatories and science centers have been opening their doors to the public on special occasions, such as Astronomy Day. However, for less than a decade, astrotourism has been the constant presence of tourists alongside professional astronomers, especially on weekends. They have made it possible by following all the principles. Until the early 1990s, one of the most important countries in the world to host the world's largest astronomical observatories was the Soviet Union. The Caucasus region in the former Soviet Union hosted very important observatories due to its high altitudes, pure nature, and very low amount of light pollution and, of course, the proper weather in warm seasons. Byurakan in Armenia, Abastumani in Georgia, Shamakhi in Azerbaijan, and BTA-6 in Russia are the four main collections left from that period. Fortunately, nearly two decades after the independence of the countries in the region, the restoration and updating of these observatories have been on the agenda. One of the helping arms to accelerate the revival of these observatories is to take advantage of the potential of astrotourism; especially with the location of these three countries near Iran, which has one of the largest astronomy enthusiast communities in the region.
Keywords: Astronomy